Iceland and development aid in the era of the MDGs: a case study of an Alma Ata inspired primary healthcare project in southern Malawi. (17th December 2018) - Gunnlaugsson, Geir; Einarsdóttir, Jónína
ABSTRACT: The monitoring of relevant health indicators is important in the examination of work that aims to improve health, not only globally, as for example, through the Millennium Development Goals 2000–2015, but also at the national, regional and/or sectoral, level. During the period 2000–2011, the Icelandic International Development Agency (ICEIDA) supported the strengthening of the primary healthcare system in the Monkey Bay area of Mangochi District, Malawi. Based on data collected through several evaluative approaches and the use of commonly used health indicators, we explore the overall performance and constraints of the services provided by ICEIDA during project implementation. Structural and diverse process indicators provided evidence that access to governmental services improved during the project period. The population expressed satisfaction with the ongoing improvement of the healthcare services they felt were of good value and quality. During the MDG era, Malawi succeeded in decreasing the under-5 mortality rate by 2/3 (MDG4 target), and maternal mortality by 66% by implementing evidence based interventions similar to those ICEIDA supported in the Monkey Bay area. Albeit small, ICEIDA's support was a relevant, effective, and efficient approach to strengthen primary healthcare services in the Monkey Bay area, resulting in tangible and sustainable benefits for the Monkey Bay communities, that may also be applicable in other settings.